Chapter 9 The essence of rage Galen on emotional disturbances and their physical correlates - Singer, P.N (Oxford University Press, 2017)
In the present paper I aim to explore the related area of how, for Galen, emotional states - the soul's affections, or pathē - are connected with bodily states. I shall be doing this largely on the basis of texts which are much less well studied - even amongst Galen scholars - than those just mentioned, and in particular ones which are not overtly works of 'psychology' or soul theory at all. In the process I shall be focussing on one particular group of common, we might say everyday, mental or emotional disturbances which Galen discusses, in some detail, in relation to their physical correlates. It is, indeed, striking that most of the detailed material that Galen offers in this area - most of the discussion of this particular set of disturbances - appears, not in his specific work on the affections of the soul, Aff. Pecc. Dig., nor in the other most obviously psychological works, PHP or QAM, but in a range of more general, medical works on disease, health and diagnosis.